Nanoscale residual stress and microstructure gradients across the cutting edge area of a TiN coating on WCCo. (June 2020) - Meindlhumer, M.; Jäger, N.; Spor, S.; Rosenthal, M.; Keckes, J.F.; Hruby, H.; Mitterer, C.; Daniel, R.; Keckes, J.; Todt, J.
Abstract: The lifetime of coated cutting tools is decisively influenced by residual stress gradients across cutting edges. Here, cross-sectional X-ray nanodiffraction with a beam size of  35   ×   25 nm 2 was used to retrieve gradient properties of a ~2 µm thick TiN coating on WCCo substrate. The planar regions next to the edge exhibit gradual and constant stress profiles with anisotropic defect build-ups on the flank and rake faces, respectively. Directly at the edge, nonlinear lateral and cross-sectional compressive residual stress gradients up to about −3 GPa were observed. The coating's 〈111〉 fibre texture orientation correlates with the orientation of principal stress components. Graphical abstract: Image, graphical abstract